2019
DOI: 10.3389/fenrg.2019.00122
|View full text |Cite
|
Sign up to set email alerts
|

Energy Performance of Cool Roofs Followed by Development of Practical Design Tool

Abstract: Cool/white roofing systems use paints and membranes with high solar reflectivity to reflect a portion of the incident solar radiation resulting in lowering the temperature of the exterior surfaces in respect of the conventional/black roofing systems. This study focuses on the energy performance of roofing system that is being used in buildings of the Gulf Cooperation Council countries when this roof is exposed to a hot and humid climatic conditions in Saudi Arabia. The long-term moisture performance of the whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…The proposed roof system included some unsustainable materials that worsen the environmental impacts during the building life cycle. Saber and Maref (2019) analyzed a roof system which consisted of ceramic tile "light color," mortar, sand screed, insulation layer, waterproofing, sand screed, foam concrete, and reinforced concrete slab as shown in Fig. 3-B.…”
Section: Testing Flat Roof Systems Using Numerical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed roof system included some unsustainable materials that worsen the environmental impacts during the building life cycle. Saber and Maref (2019) analyzed a roof system which consisted of ceramic tile "light color," mortar, sand screed, insulation layer, waterproofing, sand screed, foam concrete, and reinforced concrete slab as shown in Fig. 3-B.…”
Section: Testing Flat Roof Systems Using Numerical Analysismentioning
confidence: 99%
“…Not all research has conducted an economic evaluation for these developments despite its importance to homeowners (Mayhoub et al, 2019;Ingrao et al, 2016;Aktemur and Atikol, 2017;Salandin and Soler, 2018;Tejedor et al, 2017;Guillen et al, 2014;Asdrubali et al, 2014) and also the use of sustainable materials are not widely adopted. Many works were also conducted to improve building thermal performance by adding reflective coating and insulation layers but also without economic evaluation of these developments (Mohamed et al, 2016;Saber and Maref, 2019;Radhi et al, 2017;Ascione et al, 2018). On the other hand, adding a plant layer to building envelope systems has been tested which significantly improved building thermal performance during the summer season; however, the side effect of these solutions was recorded in the increase of the relative humidity (Nadia et al, 2013;Gagliano et al, 2015;Bevilacqua et al, 2015;Zhao et al, 2013;Tang and Zheng, 2019).…”
Section: Aim and Objectives Of This Researchmentioning
confidence: 99%
“…It was concluded that an insulation of 12 to 14 cm must be adopted in all cities to avoid penalties during heating periods. Sabe et al [10] assessed the energy performance according to the insulation thickness and reflectivity (white or black) of the roof in hot, humid climatic conditions in Saudi Arabia. It was observed that if a white roof were applied to a building, the use of insulation on the roof could be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…As the reflectivity increases, the cooling load decreases [10,11,65]. This phenomenon occurs because the increase in the reflectivity of the solar radiation energy prevents the temperature rise of the external wall, thereby reducing the amount of heat transfer to the indoor space [24,25].…”
mentioning
confidence: 99%
“…These are called "cool coatings" since they show a high thermal emittance which induces a fast heat release to the surrounding environment. Cool coatings, also for roof applications, have been widely studied [7,[20][21][22][23][24][25][26][27][28][29][30][31].…”
mentioning
confidence: 99%